2005
DOI: 10.1002/dvdy.20493
|View full text |Cite
|
Sign up to set email alerts
|

Origin, fate, and function of the components of the avian germ disc region and early blastoderm: Role of ooplasmic determinants

Abstract: In the avian oocytal germ disc region, at the end of oogenesis, we discerned four ooplasms (␣, ␤, ␥, ␦) presenting an onion-peel distribution (from peripheral and superficial to central and deep. Their fate was followed during early embryonic development. The most superficial and peripheral ␣ ooplasm plays a fundamental role during cleavage. The ␤ ooplasm, originally localized in the peripheral region of the blastodisc, becomes mainly concentrated in the primitive streak. At the moment of bilateral symmetrizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 102 publications
1
27
1
Order By: Relevance
“…Indeed, the lunulashaped region of the epiblast giving rise to the primitive streak is still referred to as 'Rauber's sickle' (Rauber 1875b(Rauber , 1876aCallebaut and Van Nueten 1994). Most recent data corroborate Rauber's conclusion when relating 'Rauber's sickle' to the gastrulation organizer of the avian blastoderm (Callebaut 2005(Callebaut : 1203 cf. Lawson and Schoenwolf 2003).…”
Section: A B C Dmentioning
confidence: 57%
“…Indeed, the lunulashaped region of the epiblast giving rise to the primitive streak is still referred to as 'Rauber's sickle' (Rauber 1875b(Rauber , 1876aCallebaut and Van Nueten 1994). Most recent data corroborate Rauber's conclusion when relating 'Rauber's sickle' to the gastrulation organizer of the avian blastoderm (Callebaut 2005(Callebaut : 1203 cf. Lawson and Schoenwolf 2003).…”
Section: A B C Dmentioning
confidence: 57%
“…In our present study, we have demonstrated that in the same species (Gallus domesticus) and the same blastoderm both mosaic development or regulation phenomena can be obtained, only by the different geometric distribution of Rauber's sickle material in the isolated blastoderm fragment. Rauber's sickle material that contains g ooplasm (Callebaut, 1994(Callebaut, , 2005, regulates early embryonic patterning (gastrulation) by its inducing effect on the upper layer Fig. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Stereomicroscopic Polaroid photographs were taken in the same direction at the beginning, during, and at the end of the culture period. Fixation and embedding in paraffin were performed as mentioned in earlier studies (Callebaut, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it would be reasonable to think that induction would be the modality adopted in PGC specification in avian embryos. Despite this regulative capacity, it was proposed that different ‘ooplasms’ (maternally derived substances present in the egg cell), localised in different regions of the mature oocyte, are inherited by different portions of the developing embryo: pPGCs would inherit the so‐called ‘δ ooplasm’, localised in the deep central area 67, 68. This was the first support of what became the current view on PGC specification in the avian embryo: maternally produced germ plasm determines PGCs.…”
Section: A Historical Perspective On Avian Pgcs: Is Maternal Specificmentioning
confidence: 99%